Rancang Bangun Virtual Tour Dalam Mempromosikan Pariwisatawan Lokal Pantai Santolo Menggunakan Metode MDLC - Baswardono, Wiyoga; Akbar , Fikri Faisal (Institut Teknologi Garut, 2025)
Santolo Beach in Garut, West Java, is a tourist destination with great natural potential, but it is not widely known due to limited promotional strategies that are still conventional in nature. This study aims to develop a website-based digital promotional media by applying 360-degree virtual tour technology using the Multimedia Development Life Cycle (MDLC) method. The MDLC method consists of six stages, namely: Concept, Design, Material Collecting, Assembly, Testing, and Distribution. In this development, 17 360° panoramic images, 32 tourist spot images, and other multimedia elements were collected to create an interactive and informative website display. The final result shows that the virtual tour website is capable of providing an exploration experience and making it easier for users to get to know tourist destinations digitally. This media is also an effective and modern solution in supporting the promotion of Santolo Beach tourism, with the hope of significantly increasing its attractiveness and the number of tourist visits.